Chinese outbound tourism to Europe - Wei, Cheng; Tang, John C.S.; Zimmerman, Willi; Donyaprueth Krairit; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
Tourism industry is one of the fastest growing industries in China's economy. The Chinese outbound tourism industry is one of important components that constitute Chinese tourism industry. The Chinese outbound tourism market has been expanding rapidly in recent years. Europe is becoming an emerging destination for Chinese outbound tourists. A research for Chinese outbound tourism to Europe becomes necessary. The objective of the study is to review the development of Chinese outbound tourism market and find the reasons that boom Chinese outbound tourism market. Based on the analysis for the China's outbound tourism policy, the characteristics of Chinese tourists in Europe, and the competitiveness of main European destinations, the findings of the research reveal that the development of Chinese outbound tourism market completely depends on the policies of Chinese government, and that the market of Chinese outbound tourism and the consumption model of Chinese outbound tourists are immature. Based on the findings of the research, some conclusions and recommendations are developed. They may be helpful to the tourism industry investors and operators who would like to enter the Chinese outbound tourism market for Europe
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2006
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Keywords: Tourism -- China; Tourism -- Europe